Analysis of Taxpayer's Level of Understanding and Awareness of Tax Compliance on Entrepreneurs/Traders in Gunungsitoli City - Niken Rahmadyah; Wahyu Syarvina (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2022)
Taxes are one of the sources of state revenue, by paying taxes we already have good intentions to participate in helping development whose benefits are for the benefit of all the people. Tax is state income that is collected directly from the public in the form of contributions, the tax taken will be accumulated in accordance with the provisions of the law, one of the taxes that must be paid is income tax paid by taxpayers, which is imposed by individuals or companies based on the results of their income. This study aims to analyze the level of understanding and awareness of taxpayers on tax compliance for entrepreneurs/traders in carrying out their tax obligations. The population in this study are entrepreneurs/traders who have businesses in the Gunungsitoli City area. The sampling technique was purposive sampling with a total sample of 40 respondents. This study uses primary data, namely questionnaires. This study uses quantitative methods with multiple regression analysis models, including t test and f test processed using the SPSS program. The results obtained indicate that the level of understanding and awareness of taxes has a significant effect on tax compliance, seen from the significance level of 0.004 or less than 0.05, then for the Fcount value of 6.365 or greater than Ftable of 3.25 in other words Fcount > Ftable , then according to the basis of decision making in the F test, it can be concluded that the regression model can be used to predict tax compliance or it can be said that the two independent variables, namely taxpayer awareness and level of understanding simultaneously or jointly affect tax compliance.